Raphtory: the temporal graph engine for Rust and Python - Steer, B; Arnold, NA; Ba, CT; Lambiotte, R; Yousaf, H; Jeub, L; Murariu, F; Kapoor, S; Rico, P; Chan, R; Chan, L; Alford, J; et al. (Open Journals, 2024)
Raphtory is a platform for building and analysing temporal networks. The library includes methods for creating networks from a variety of data sources; algorithms to explore their structure and evolution; and an extensible GraphQL server for deployment of applications built on top. Raphtory’s core engine is built in Rust, for efficiency, with Python interfaces, for ease of use. Raphtory is developed by network scientists, with a background in Physics, Applied Mathematics, Engineering and Computer Science, for use across academia and industry.